Cutting propagation of Baccharis trimera (Less.) A.R de Candolle (Revista Brasileira de Plantas Medicinais, 2000)
Some experiments were conducted into a greenhouse to verily the effect of substrate, IBA (indol butyric acid), position and culling length in the Baccharis trimera propagation Cuttings collected of new shoots, without ramifications, were used in all experiments. The substrates were the following vermiculite, sand, soil and carbonized rice hulls. The statistical design was completely randomized with 4 replicates. The IBA concentratios were the following: 0, 500. 1000. 1500 and 200Qmg,LThe statistical design was the same ol the experiment with substrate. In the third experiment was tested the following cutting positions: apical, middle and basal. The statistical design was completely randomized with 5 replicates. In the last experiment was tested the following cutting length: 5, 10, 15 and 20 cm, The statistical design was in randomrzed blocks with 4 replicates. The expenments with substrates and cutting length were conducted into a greenhouse and irrigated once each two days. The others experiments were conducted into a intermitent mist chamber with irrigation each 30 minutes. The best substrate was the carbonized rice hulls, that showed the highest rooting system development, the smalest mortality and the highest shoot growth The IBA has not significanty affected the rooting percentage, which rate was 93.5%, but showed effect in relation al the number of roots per cutting, which the IBA concentration at 2000mg.L-1 (10,3 roots/cutting) was higher than control (6,3 roots/cutting), but didn’t differ the others. The root number por cutting and the shoot length per cutting increased with tha cutting length. The cutting position has not significantly affected the rooling cuttings, but the basal cuttings showed the smallest root number per cutting, the highest mortality and the smallest percent of culling with shoot. The Baccharis trimera propagation can be possible by cutting with 15 or 20 cm colected of the apical and middle portion of the shoots, in substrate of carbonized rice hulls, without IBA application.